Nonlinear co-integration between unemployment and economic growth in South Africa - Phiri, Andrew (Managing global transitions, 2014)
In this paper, a momentum threshold autoregressive (MTAR) model is used to evaluate nonlinear equilibrium reversion between unemployment and economic growth for South African data between the periods 2000-2013. To attain this objective we estimate the first-difference and the gap model variations of Okun's specification. For the latter model variation, we employ three de-trending methods to obtain the relevant "gap" data; namely, the Hodrick-Prescott (HP) filter, the Baxter-King (BK) filter and the Butterworth (BW) digital filter. A common finding from our empirical analysis is that Okun's law holds concretely for South African data regardless of the model specification or the de-trending technique that is used. Moreover, our analysis proves that unemployment granger causes economic growth in the long-run, a result which may account for the jobless-growth phenomenon experienced by South Africa over the last decade or so.
Keywords: brezposelnost; unemployment; economic growth; gospodarska rast; Okunov zakon; Okun's law; Južna Afrika; nonlinear unit root tests; model MTAR; Butterworth high-pass filter; nelinearni "unit-root" testi; nelinearna povezava; nelinearni Grangerjevi testi; filter Hodrick-Prescott; filter Baxter-King; visokofrekvenčni filter Butterworth; South Africa; MTAR model; nonlinear co-integration; nonlinear Granger tests; Hodrick-Prescott filter; Baxter-King filter